Mechanical Properties of 3D Printed Polypropylene (PP) Reinforced with Kenaf Particles - Nabil Fikri Bin Sharif fudin,; Wahab, Md Saidin (Research Progress in Mechanical and Manufacturing Engineering, 2024)
3D printing builds objects layer upon layer, offering unprecedented design freedom and customization since the core of 3D printing is the layer-by-layer construction of objects. This study objective is to determine the mechanical properties of fabricated PP and kenaf/PP composite specimens in terms of tensile, and impact test. The scope of this study is Specimen printing variance of PP, 0 wt.% Kenaf/PP, 3 wt.% Kenaf/PP, 5 wt.% Kenaf/PP, and 7 wt.% Kenaf/PP. All the specimen sample will be printed using Fused Deposition Modelling (FDM) and Polypropylene with Kenaf are the material that will be used in this study. The result of average tensile strength showed 5 wt.% kenaf/PP were highest than any variance which is 18.2507MPa. While the highest average for impact strength is 3 wt.% kenaf/PP which is 0.077J.